Myrosinase: insights on structural, catalytic, regulatory, and environmental interactions. (19th May 2019) - Bhat, Rohini; Vyas, Dhiraj
Abstract: Glucosinolate–myrosinase is a substrate-enzyme defense mechanism present in Brassica crops. This binary system provides the plant with an efficient system against herbivores and pathogens. For humans, it is well known for its anti-carcinogenic, anti-inflammatory, immunomodulatory, anti-bacterial, cardio-protective, and central nervous system protective activities. Glucosinolate and myrosinase are spatially present in different cells that upon tissue disruption come together and result in the formation of a variety of hydrolysis products with diverse physicochemical and biological properties. The myrosinase-catalyzed reaction starts with cleavage of the thioglucosidic linkage resulting in release of a D-glucose and an unstable thiohydroximate-O-sulfate. The outcome of this thiohydroximate-O-sulfate has been shown to depend on the structure of the glucosinolate side chain, the presence of supplementary proteins known as specifier proteins and/or on the physiochemical condition. Myrosinase was first reported in mustard seed during 1939 as a protein responsible for release of essential oil. Until this date, myrosinases have been characterized from more than 20 species of Brassica, cabbage aphid, and many bacteria residing in the human intestine. All the plant myrosinases are reported to be activated by ascorbic acid while aphid and bacterial myrosinases are found to be either neutral or inhibited. Myrosinase catalyzes hydrolysis of the S- glycosyl bond, O- β glycosyl bond, and O- glycosyl bond. This review summarizes information on myrosinase, an essential component of this binary system, including its structural and molecular properties, mechanism of action, and its regulation and will be beneficial for the research going on the understanding and betterment of the glucosinolate–myrosinase system from an ecological and nutraceutical perspective.